Family Matters: Bugis Genealogies And Their Contribution To Austronesian Studies - Caldwell, Ian; Wellen, Kathryn (Penerbit Universiti Sains Malaysia (USM Press), 2016)
Early Bugis written sources consist largely of genealogies. Assuming no significant loss of other genres, it is clear that genealogies were central to Bugis historical record keeping. The paper sets out to explain why genealogies were first written down, what purpose they served, and why they were repeatedly added to and copied. It argues that written genealogies had no function as practical documents. Instead, they owed their existence directly to the development of writing around 1400 CE, and to the status that their possession conferred on their owners. The article sets out what historians can learn from genealogies of South Sulawesi prior to the arrival of the first Western visitors. It draws attention to a threegeneration myth of origin similar to that found in the Malay Hikayat Banjar, and argues that this myth was central to agricultural fertility, and the right to rule.